Diversity, Evenness, and Dominance Index of Amphibians in Lowland Rain Forest: A Case of Anura Ordo in Way Kambas National Park, Indonesia - Dewi, Bainah Sari; Zania, Azalia; Damayanti, Evi; Kuswandono; Hilmanto, Rudi (Jurnal Sylva Lestari, 2024)
Amphibian is a vertebrate animal whose life is always associated with water. Anura ordo has the most extensive spread in Indonesia. A study on amphibians in Way Kambas National Park has never been conducted. Therefore, the purpose of this research was to find out the diversity, evenness, dominance, temperature, and humidity of three various habitats of amphibians of Anura ordo in Rawa Bunder National Park Management Resort (RPTN Rawa Bunder), Way Kambas National Park, Indonesia. Amphibian data was collected using the visual encounter survey and line transect methods. The results of this research discovered amphibians in 6 families, which consisted of 13 species of amphibians based on observations in three different habitat types. The Shannon-Wiener diversity index (H') was categorized as moderate with the H' of 1.91–2.27. The evenness index (E) was considered stable, ranging between 0.87–0.91. The dominant index (D) falls into the low dominance group, with the D value ranging between 0.13–0.19. This shows that no dominant species is present. Keywords: Anura, amphibians, biodiversity, predominance, Way Kambas National Park